Anti-Corruption from Below. Social Movements Against Corruption in Late Neoliberalism - della Porta, Donatella (PARTECIPAZIONE E CONFLITTO, 2018)
In the last decades, a growing awareness has emerged in progressive social movements about the relevance of corruption as a hidden factor that negatively influences political and economic decision-making processes in both liberal-democratic and authoritarian regimes. Rampant corruption has been denounced by social movements, which have developed specific diagnostic and prognostic frames as well as knowledge and practices for the social accountability of political and economic powers. This contribution maps some of the characteristics of civil society as anti-corruption actors, reflecting on the theoretical challenges they present for social movement theory and for research on corruption and anti-corruption. In order to understand the emergence and outcomes of these mobilizations against corruption, it bridges two bodies of literature which have only very rarely crossed paths: corruption studies and social movement studies. Departing from the traditional visions of anti-corruption from below within corruption studies, the article brings upon social movement studies in order to synthetize some of the main context, organizational forms and framing of (anti-)corruption in today’s contentious politics.